2013
DOI: 10.5267/j.msl.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Narcissism in Iranian auditing profession

Abstract: This study investigates the level of Narcissism among 185 Iranian auditors groups and narcissism has been used to describe people behavior in people groups. The present study uses a questionnaire to measure Narcissism and to examine the hypotheses of the paper analysis of variance and T-test are used. The results of testing hypotheses show that the level of narcissism was significantly different in auditors groups in private sector. However, in public sector, the difference between narcissistic personality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Raskin and Terry (1988) declare that the following seven components characterize narcissism, namely, power, selfishness, prominence, pride, stability, reduced entitlement and self-sufficiency. Narcissism is used for describing behaviors in organizations, and recent studies on finance, accounting and auditing indicate that narcissism describes firm behavior (Banimahd et al, 2013). Banimahd et al (2013) declare that when an auditor benefits from a high narcissism level, this may affect the auditor's judgment about the clients' performance and lead to an incorrect and biased report about firm performance.…”
Section: Auditor Narcissismmentioning
confidence: 99%
See 1 more Smart Citation
“…Raskin and Terry (1988) declare that the following seven components characterize narcissism, namely, power, selfishness, prominence, pride, stability, reduced entitlement and self-sufficiency. Narcissism is used for describing behaviors in organizations, and recent studies on finance, accounting and auditing indicate that narcissism describes firm behavior (Banimahd et al, 2013). Banimahd et al (2013) declare that when an auditor benefits from a high narcissism level, this may affect the auditor's judgment about the clients' performance and lead to an incorrect and biased report about firm performance.…”
Section: Auditor Narcissismmentioning
confidence: 99%
“…Narcissism is used for describing behaviors in organizations, and recent studies on finance, accounting and auditing indicate that narcissism describes firm behavior (Banimahd et al, 2013). Banimahd et al (2013) declare that when an auditor benefits from a high narcissism level, this may affect the auditor's judgment about the clients' performance and lead to an incorrect and biased report about firm performance. Moreover, most of the studies on accounting, for example, Cohen et al (2010), show that narcissism is positively associated with recent frauds and scandals.…”
Section: Auditor Narcissismmentioning
confidence: 99%
“…Going through the results, we find that (1) male auditors are more narcissistic than female auditors, but this difference is not statistically significant at 5% level. Banimahd et al. (2013) reported that the average of narcissism is different between male and female auditors and Grijalva et al.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Cohen et al (2010) also reveal a positive and significant relationship between auditor narcissism, fraud and financial scandals. Banimahd et al (2013) perceive that narcissism is significantly different among auditor groups in the private section. However, in the public section, such a relationship between narcissistic characters is not significant among auditor groups.…”
Section: Theoretical Issuesmentioning
confidence: 96%